MBA offered at Biotech Corporation - Sorooshian, Shahryar; M., Waris; Senthil Kumar , T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (FIM-UMP, 2016)
This program was conceived as an integration of theory and industrial experience to create potential leaders who would be able to solve complex issues systematically and creatively.